2022
DOI: 10.3389/fnagi.2022.889983
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Theta Burst Stimulation Ameliorates Cognitive Deficit and Attenuates Neuroinflammation via PI3K/Akt/mTOR Signaling Pathway in Alzheimer’s-Like Disease Model

Abstract: Neurodegeneration implies progressive neuronal loss and neuroinflammation further contributing to pathology progression. It is a feature of many neurological disorders, most common being Alzheimer’s disease (AD). Repetitive transcranial magnetic stimulation (rTMS) is a non-invasive stimulation which modulates excitability of stimulated brain areas through magnetic pulses. Numerous studies indicated beneficial effect of rTMS in several neurological diseases, including AD, however, exact mechanism are yet to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 78 publications
1
9
0
Order By: Relevance
“…On the other hand, under certain pathological conditions, astrocytes become one of the main sources of detrimental free radicals and directly promote neural damage ( Chen et al, 2020 ). Astrocytes can directly or indirectly respond to electrical activity and, based on accumulating evidence, now it is strongly implicated that astrocytes are cellular effectors of TMS ( Cullen and Young, 2016 ) and iTBS, respectively, ( Dragic et al, 2020 ; Dragić et al, 2021 ; Stanojevic et al, 2022 ; Stekic et al, 2022 ). Our results showed STZ-induced GFAP/VIM/C3 colocalization in the hippocampus, which was a marker of reactive astrocytes ( Dragić et al, 2019 ), specifically in fimbria, which was adjacent to lateral ventricles where the toxin had been applied, indicating reactive astrogliosis persists even 8 weeks after STZ administration.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, under certain pathological conditions, astrocytes become one of the main sources of detrimental free radicals and directly promote neural damage ( Chen et al, 2020 ). Astrocytes can directly or indirectly respond to electrical activity and, based on accumulating evidence, now it is strongly implicated that astrocytes are cellular effectors of TMS ( Cullen and Young, 2016 ) and iTBS, respectively, ( Dragic et al, 2020 ; Dragić et al, 2021 ; Stanojevic et al, 2022 ; Stekic et al, 2022 ). Our results showed STZ-induced GFAP/VIM/C3 colocalization in the hippocampus, which was a marker of reactive astrocytes ( Dragić et al, 2019 ), specifically in fimbria, which was adjacent to lateral ventricles where the toxin had been applied, indicating reactive astrogliosis persists even 8 weeks after STZ administration.…”
Section: Discussionmentioning
confidence: 99%
“…In the pathological process of AD, the PI3K/Akt-mTOR signaling is over-activated, leading to neuronal hyperactivity, transmitting wrong signals, and promoting SPs deposition [ 35 , 36 ]. There is growing evidence that enhancing neuronal autophagy levels by inhibiting activation of the PI3K/Akt-mTOR pathway can promptly clear SPs and tau proteins in the AD brain [ 37 , 38 ]. Meanwhile, previous studies have reported that scoparone promoted autophagy and attenuated the inflammatory response by blocking the PI3K/Akt-mTOR pathway [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…There was a 10 s rest period between each sequence, culminating in a total stimulation time of 192 s per session. The intensity of the magnetic stimulation was maintained at 35% of the device's maximum output, generating a magnetic field strength of 690 mT [17,23]. Animals were gently held during stimulation while they were allowed to move freely during the 10 s interval between restraints.…”
Section: Theta Burst Stimulation Protocolmentioning
confidence: 99%
“…Intermittent theta burst stimulation (iTBS) is a specialized rTMS protocol that elicits an LTP-like increase in cortical excitability, and is proving to be an attractive and superior choice for neuromodulatory treatments in clinical disorders, mainly due to the rapid onset of modulatory effects compared to conventional rTMS [16]. In addition, our team's research has demonstrated the marked efficacy of iTBS in attenuating inflammation and oxidative stress in various models of neurodegenerative disease [17][18][19][20][21]. However, the precise effects of iTBS on oxidative stress parameters in the context of PD remain largely unexplored.…”
Section: Introductionmentioning
confidence: 99%